Developing Writing Skills in Descriptive Text Using the Dictogloss Technique of Senior High School Students - Defriansyah Safei; Jenny Elvinna (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
Dictogloss is a teaching technique to help teachers in the teaching and learning process, particularly in teaching descriptive text. This study was aimed at finding out whether or not there were any significant differences between students who were taught by using Dictogloss and students who were not. There were 90 students of tenth grade MAN 2 Palembang involved in this investigation comprising two groups, 45 students of the experimental group and 45 students of the control group. The Purposive sampling technique also was used in this study. The writers used a non-equivalent group design. They taught the experimental group students to write descriptive writing by using the dictogloss technique, meanwhile, the control group students taught by using the lecturing method. The data from two groups were collected from the result of the pretest and post-test scores which were analyzed to get the main score differences. The writers found out that the mean score of the experimental group improved significantly from 63.8 pretest to 73.4 in the posttest. The results of the Independent T-test showed that the mean score between the control and experimental groups was 4.664. It meant that there was a very significant difference between the two groups which was caused by the technique given to the experimental group.